Upaya Meningkatkan Hasil Belajar Siswa Materi Huruf Hijaiyah dan Harakat Menggunakan Media Plastisin - Faizah; Fitriyah, Siti Nur (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2021)
The low results of students' scores on PAI material of hijaiyah letters theme and their harat are the main problems in this research. The reason is, students 'sociological background, students' thinking ability, less creative and innovative teachersin using learning media. This study aims to improve learning outcomes of "I Love Al-Quran_Huruf Hijaiyah and Its People" themefor grade I students of SDN Cengklik Semester 1.Using Classroom Action Research method and carried out in three cycles, namely pre-cycle, cycle I and cycle II then reflected with a comparative descriptive. Hypothesis test results obtained that the use of plasticine media can improve learning outcomes of Hijaiyah and Harakat Letters material for grade I students of SDN Cengklik Semester 1.From the initial conditions, the average achievement is 67 and the final condition is an average of 85, which means that the student's score increases 27%.